The Potention of Nipah Fiber (Nypa fruticans Wurmb.) in The Production of Nata Fruticans Using Soybean Sprouts as a Source of Nitrogen - Fitratul Aini; Hasnaul Maritsa; Hesti Riany (Biota, 2020)
Nypa is a mangrove plant that acts as a food source, such as nata. Research has shown that nipah plant waste, such as frond fibers and nipah fruit skin fibers, can be used as a raw material in making nata fruticans. The purpose of this study was to determine the potential of nipah fiber (Nypa fruticans Wurmb.) in nata production using soybean sprouts as a nitrogen source. The samples of nipah fiber (Nypa fruticans) used were leaves (DN), midrib (PN) and fruit skin (KB), taken in the Kuala Tungkal area, West Tanjung Jabung Regency, Jambi Province. This research method includes making the mother solution, making nata starter, and producing nata sheet by using soybean as a source of nitrogen with a concentration of 5%, 10% and 15% and ZA as a control. The results of this study indicate that the best volume and thickness of nata fruticans can be seen from the midrib substrate with a concentration of 10% soybean sprouts. The yields produced for all treatments were still lower compared to controls. Meanwhile, the water content of all treatments was better than the control. The best quality of Nata Fruticans based on thickness, yield and average moisture content was generally obtained from the substrate from the leaf midrib fibers with a concentration of 10% soybean sprouts